Characteristics and treatment measures of tunnel collapse in fault fracture zone during rainfall: A case study. (March 2023) - Chen, Longlong; Wang, Yaqiong; Wang, Zhi-Feng; Fan, Feifei; Liu, Yong
Highlights: The characteristics and mechanism of tunnel collapse were analyzed. A 3D discrete element model was established to simulate the process of tunnel collapse. The failure mechanism of broken rock caused by water seepage was analyzed. The treatments of collapse were proposed and analyzed. Abstract: This paper analyzes the characteristics and mechanism of the collapse of a tunnel in Wenzhou in fault fracture zone during rainfall based on the failure theory of surrounding rock, three-dimensional discrete element numerical simulation and in-situ deformation monitoring. It was demonstrated that the continuous erosion and expansion of rock fissures caused by the scouring of water seepage on surrounding rock fissures is the main reason for the continuous reduction of surrounding rock stability in fault fracture zone after tunnel excavation. The failure process of surrounding rock was simulated by a three-dimensional discrete element model, and the results were consistent with the engineering practice. Treatment measures of collapse are adopted, including surface grouting, grouting in tunnel, and pipe-roof. The effect of reinforcement was evaluated through monitoring. The lessons and experience in this case has reference value for the prevention of tunneling collapse in fault fracture zone.